Biological Membrane Mimetics to Study Radiation Induced Damages by NMR Spectroscopy: Application to Study Erythrocyte Membranes - A. G. Shahkhatuni; Shahkhatuni, A. A.
The role of biological membranes as a target in biological radiation damage remains unclear. In the present article, we show that the structural, biochemical and biophysical changes of a simple biological membrane, i.e. human erythrocyte membranes, which is altered after exposure, could be studied by membrane mimetics and conventional NMR spectrometers.
Keywords: Physics; Cross-Disciplinary